THE FUNCTIONS OF THE FAMILY: TRADITIONS AND CURRENT STATE - Alimova, B M; Musaeva, M K (History, Archeology and Ethnography of the Caucasus, 2016)
The article deals with the family as a multifunctional social institution. The authors analyze the family functions of two types (of personal and social orientation), which have been traditional features of the family (household and consumer, reconstructive; sex-role, economic-financial, educational functions, organization of leisure and recreation of family members, etc.). The authors of the article show that many of these functions have undergone modification and nowadays have new content, some of them have lost their significance at all. The current state of the majority of the family functions and the role of the state in the transformation of traditional functions are considered in the article.
Keywords: peoples of Dagestan; family; function; tradition; transformation; role of the state